Early breastfeeding experiences of adolescent mothers: a qualitative prospective study - Smith Paige Hall; Coley Sheryl L; Labbok Miriam H; Cupito Susan; Nwokah Eva (BMC, 2012)
Abstract Background Teen mothers face many challenges to successful breastfeeding and are less likely to breastfeed than any other population group in the U.S. Few studies have investigated this population; all prior studies are cross-sectional and collect breastfeeding data retrospectively. The purpose of our qualitative prospective study was to understand the factors that contribute to the breastfeeding decisions and practices of teen mothers. Methods This prospective study took place from January through December 2009 in Greensboro, North Carolina in the U.S. We followed the cohort from pregnancy until two weeks after they ceased all breastfeeding and milk expression. We conducted semi-structured interviews at baseline and follow-up, and tracked infant feeding weekly by phone. We analyzed the data to create individual life and breastfeeding journeys and then identified themes that cut across the individual journeys. Results Four of the five teenagers breastfed at the breast for nine days: in contrast, one teen breastfed exclusively for five months. Milk expression by pumping was associated with significantly longer provision of human milk. Breastfeeding practices and cessation were closely connected with their experiences as new mothers in the context of ongoing multiple roles, complex living situations, youth and dependency, and poor knowledge of the fundamentals of breastfeeding and infant development. Breastfeeding cessation was influenced by inadequate breastfeeding skill, physically unpleasant and painful early experiences they were unprepared to manage, and inadequate health care response to real problems. Conclusions Continued breastfeeding depends on a complex interplay of multiple factors, including having made an informed choice and having the skills, support and experiences needed to sustain the belief that breastfeeding is the best choice for them and their baby given their life situation. Teenagers in the US context need to have a positive early breastfeeding experience, be able to identify and claim a reliable support system supportive of breastfeeding, and gain through their experience, a belief in their own agency and competency as mothers.